2020
DOI: 10.3390/ani10020337
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Trypsin-Hydrolyzed Camel and Cow Whey and Their Fractions

Abstract: Antibacterial peptides were isolated and purified from whey proteins of camel milk (CaW) and cow milk (CoW) and their antimicrobial activities were studied. The whey proteins were hydrolyzed using trypsin, and the degree of hydrolysis was identified by gel electrophoresis. The whey hydrolysate (WH) was purified using ultrafiltration and Dextran gel chromatography to obtain small peptides with antibacterial activity. The effect of the antimicrobial peptides on the morphology of bacterial strains was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…The samples were fixed using formalin, embedded in paraffin, sliced into sections, and stained using hematoxylin and eosin, and then observed using a light microscope, as described previously ( Zhou et al, 2018 ). For ultrastructure observation, the samples were sequentially fixed using glutaraldehyde and then osmium tetroxide, dehydrated, embedded, sliced into ultrathin sections, stained using uranyl acetate and lead citrate, and observed using a transmission electron microscope ( Wang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The samples were fixed using formalin, embedded in paraffin, sliced into sections, and stained using hematoxylin and eosin, and then observed using a light microscope, as described previously ( Zhou et al, 2018 ). For ultrastructure observation, the samples were sequentially fixed using glutaraldehyde and then osmium tetroxide, dehydrated, embedded, sliced into ultrathin sections, stained using uranyl acetate and lead citrate, and observed using a transmission electron microscope ( Wang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…When LMPC was tested, a zone of inhibition in an agar plate of test microorganisms was not found; however, some investigators reported that native whey proteins offer antibacterial activity [107]. Antibacterial activity in two isolated whey proteins, lactoferrin [108,109] and lactoperoxidase [110,111], has also been reported by some investigators.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The anti-microbial activities of whey proteins from camel milk have been widely studied [ 5 , 56 ]. These whey proteins have higher anti-microbial activities compared to those of cow milk proteins [ 57 ]. It has been shown that camel milk whey proteins significantly inhibited the growth of pathogenic strains of E. coli and L. monocytogenes [ 28 ].…”
Section: The Anti-microbial and Antioxidant Properties Of Camel Milkmentioning
confidence: 99%